2012
DOI: 10.1186/1471-2458-12-57
|View full text |Cite
|
Sign up to set email alerts
|

Participation in and attitude towards the national immunization program in the Netherlands: data from population-based questionnaires

Abstract: BackgroundKnowledge about the determinants of participation and attitude towards the National Immunisation Program (NIP) may be helpful in tailoring information campaigns for this program. Our aim was to determine which factors were associated with nonparticipation in the NIP and which ones were associated with parents' intention to accept remaining vaccinations. Further, we analyzed possible changes in opinion on vaccination over a 10 year period.MethodsWe used questionnaire data from two independent, populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 20 publications
(22 reference statements)
6
37
1
Order By: Relevance
“…Eleven articles studied concerns about childhood vaccination in general [143][144][145][146][147][148][149][150][151][152][153][154]. The most common concerns were about adverse reactions [144][145][146][147][148][150][151][152][153][154].…”
Section: Childhood Vaccinationmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven articles studied concerns about childhood vaccination in general [143][144][145][146][147][148][149][150][151][152][153][154]. The most common concerns were about adverse reactions [144][145][146][147][148][150][151][152][153][154].…”
Section: Childhood Vaccinationmentioning
confidence: 99%
“…The most common concerns were about adverse reactions [144][145][146][147][148][150][151][152][153][154]. Other studies reported that participants believed that vaccine preventable diseases are not dangerous [147,148,150] but instead are beneficial for child development [149,150].…”
Section: Childhood Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…An anthroposophic lifestyle often includes a biodynamic diet, wool fabric for clothing and restrictive use of antibiotics and antipyretics. Anthroposophic followers are hesitant to vaccinate due to beliefs that measles infections strengthens children's development [27,[35][36][37]. The philosophy is the basis for anthroposophic medicine and the pedagogy in Waldorf schools.…”
Section: Meaning Unit (Quote)mentioning
confidence: 99%
“…Mortality rates were obtained from Statistics Netherlands, which registers mortality data from death certificates on a statutory basis. Seroprevalence data to estimate prevalences of varicella zoster, pertussis and hepatitis A were available from two cross-sectional, population-based serosurveillance studies carried out in 1995–1996 and 2006–2007 among persons aged 0 to 79 years [14,15]. The international literature was searched for additional information on the four domains of the evaluation model for each of the infectious diseases in the study population.…”
Section: Methodsmentioning
confidence: 99%